Distinct magnetic regimes through site-selective atom substitution in the frustrated quantum antiferromagnet Cs 2CuCl 4-xBr x - Cong, P; Wolf, B; De Souza, M; Krüger, N; Haghighirad, A; Gottlieb-Schoenmeyer, S; Ritter, F; Assmus, W; Opahle, I; Foyevtsova, K; Jeschke, H; Valentí, R; et al. (2011)
We report on a systematic study of the magnetic properties on single crystals of the solid solution Cs 2CuCl 4-xBr x (0 ≤ x ≤ 4), which include the two known end-member compounds Cs 2CuCl 4 and Cs 2CuBr 4, classified as quasi-two-dimensional quantum antiferromagnets with different degrees of magnetic frustration. By comparative measurements of the magnetic susceptibility χ(T) on as many as 18 different Br concentrations, we found that the in-plane and out-of-plane magnetic correlations, probed by the position and height of a maximum in the magnetic susceptibility, respectively, do not show a smooth variation with x. Instead, three distinct concentration regimes can be identified, which are separated by critical concentrations x c1 =; 1 and x c2 =2. This unusual magnetic behavior can be explained by considering the structural peculiarities of the materials, especially the distorted Cu-halide tetrahedra, which support a site-selective replacement of Cl - by Br - ions. Consequently, the critical concentrations x c1 (x c2) mark particularly interesting systems, where one (two) halide-sublattice positions are fully occupied. © 2011 American Physical Society.